High rate of epidermal growth factor receptor-mutated primary lung cancer in patients with primary breast cancer - Zeng, Tianyu; Xu, Hai; Liu, Yincheng; Sun, Chunxiao; Yang, Fan; Liang, Yan; Huang, Xiang; Fu, Ziyi; Li, Wei; Yin, Yongmei (Frontiers in Oncology, 2022)
Background: With increased survival in breast cancer, resulting from advances in treatment, patients incur the possibility of subsequent primary malignancies, especially lung cancer. The aim of this study was to assess the frequency of CT-detected pulmonary ground-glass nodules and lung cancer following breast cancer diagnosis, the associations between breast cancer and lung cancer, the pathological features of double primary cancer, and the status of epidermal growth factor receptor (EGFR) mutations in second primary lung cancer. Methods: Clinical data from more than 9000 individuals who were diagnosed with primary breast cancer at Jiangsu Province Hospital (Jiangsu, China) between January 2008 and December 2021 were retrospectively analyzed. Results: Of the 9179 patients, 55 (0.8%) were diagnosed with a second primary lung cancer, which accounted for approximately 18.4% of the pulmonary ground-glass nodules (GGNs) detected. The incidence was higher than in the general female population (standardized incidence ratio 1.4 [95% confidence interval (CI): 1.25-1.55]). Patients who experienced a second primary lung cancer exhibited a significantly higher rate of EGFR mutation (78.5%) than those with lung adenocarcinoma alone, with most exhibiting low-grade malignancy, older age, estrogen receptor negativity, low Ki67, and no lymph node metastasis. Conclusions: Breast cancer patients, especially those with low-grade malignancy, were at high risk for developing primary lung cancer. For isolated GGN in patients with high-risk factors, clinicians should insist on close follow-up. Furthermore, EGFR may play an important role in primary lung adenocarcinomas and breast cancer.